Computational model of asperity contact for the prediction of mechanical and wear behaviour in total joint replacements - Suhendra, N; Stachowiak, Gwidon (Springer, 2007)
The effect of sliding friction on the size of yielding region in the ultra high molecular weight polyethylene asperity in contact with metal was investigated. The main objective of this work was to gain an understanding of wear particle generation mechanism from the two-dimensional finite element model. To assess the influence of the parameters of interest, different friction coefficients and loading conditions were used in the numerical simulations. Results from the finite element analysis show that the increase of the yielding region is strongly influenced by the friction coefficient and the rise in the tangential force, which is related to the generation of wear particles. Finite element wear particle generation model, based on strain discontinuities, was therefore proposed. The results obtained in this study can lead to the development of an accurate finite element particle generation model that would be of use in the assessment of an artificial implant performance and their development.